2010
DOI: 10.1097/ccm.0b013e3181eaa1e7
|View full text |Cite
|
Sign up to set email alerts
|

Continuous amplitude-integrated electroencephalogram predicts outcome in hypothermia-treated cardiac arrest patients

Abstract: Continuous amplitude-integrated electroencephalogram adds valuable early positive and negative prognostic information in comatose survivors after cardiac arrest. We identified two types of postanoxic electrographic status epilepticus, which is a novel finding with possible therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
219
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(237 citation statements)
references
References 35 publications
13
219
0
5
Order By: Relevance
“…Conversely, normal voltage ([20 lV) at any time is related to a good outcome in 71 % of patients, confirming earlier data along the same lines [6]. Considering the delicacy in reliably deciding upon a voltage amplitude around 20 lV in some patients [7], other groups concentrated rather on background reactivity to stimuli, which if present during TH has been reported to herald good prognosis in as much as 86 % [8], while lack of reactivity portended a poor prognosis in a much higher rate (99 % in [9]).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Conversely, normal voltage ([20 lV) at any time is related to a good outcome in 71 % of patients, confirming earlier data along the same lines [6]. Considering the delicacy in reliably deciding upon a voltage amplitude around 20 lV in some patients [7], other groups concentrated rather on background reactivity to stimuli, which if present during TH has been reported to herald good prognosis in as much as 86 % [8], while lack of reactivity portended a poor prognosis in a much higher rate (99 % in [9]).…”
supporting
confidence: 80%
“…They reviewed all EEG recordings in the form of 5-min extracts taken at predefined intervals from the acute event (6,12,24,48, and 72 h). Blinded to patients' identity and outcome, they applied the recently published standardized American Clinical Neurophysiology Society (ACNS) critical care EEG terminology [4], correlating their data with those of other clinical investigations.…”
mentioning
confidence: 99%
“…Rewarming is a common time for seizures to occur, either because a clinical motoric component (e.g., myoclonic status epilepticus) is revealed after discontinuation of paralytics [34,35], or because sedation or hypothermia suppressed or treated the electrographic activity [35]. In addition to detecting seizures, EEG demonstration of a reactive background rhythm or a continuous pattern on amplitude-integrated EEG had a high likelihood of good neurological prognosis, despite the presence of seizures [36][37][38]. Although myoclonic status may have a worse prognosis than nonconvulsive status epileptic in the setting of cardiac arrest treated with hypothermia, myoclonic status is not homogeneous and may have a worse prognosis when "reticular" rather than when associated with an EEG correlate [39].…”
Section: Patient Selectionmentioning
confidence: 99%
“…However, another recent study on EEG reactivity between 1 and 3 days after the anoxic event had a specificity of only 94% for predicting poor outcome (5). Furthermore, in the literature burst suppression on EEG is reported to have a specificity between 85 and 100% (4, 6, 7) and post-anoxic status epilepticus on EEG had a specificity of 98% for poor outcome (6). In a recent study, low-voltage and isoelectric EEG patterns were shown to be invariably associated with poor neurological outcome 24 h after the event in patients treated with MTH and sedation with a sensitivity of 40% and a specificity of 100%, while bilaterally absent cortical SSEP had a sensitivity of only 24% after 24 h in this study (7).…”
Section: Introductionmentioning
confidence: 99%